Kinetics on Organic Removal by Aerobic Granular Sludge in Bubbled Airlift Continuous Reactor - Andik Yulianto; Nida Maisa Zakiyya; Prayatni Soewondo; Marisa Handajani; Herto Dwi Ariesyady (Journal of Engineering and Technological Sciences, 2019)
An assessment of aerobic granular sludge (AGS) in a bubbled airlift continuous reactor (BACR) was done to determine the AGS growth kinetics in the continuous reactor and the impact of varied hydraulic retention time (HRT) against the AGS structure. Sodium acetate was used as the sole carbon source with a 100:20 ratio of COD/N synthetic water. The system was operated at five variations of HRT, i.e. 12, 10, 8, 6, and 4 hours, with organic loading rate (OLR) ranging from 1.6 to 4.8 g COD/day in the BACR. Organic removal decreased from 73% to 52%, along with the increment of OLR, while HRT decreased from 12 hours to 4 hours. The kinetics of organic removal in the BACR were examined to get a better understanding of organic removal trends by AGS in a BACR. The models used for biomass growth analysis were the Monod, Contois, Grau second-order, and Stover-Kincannon kinetic models. This study showed that the best suited models for organic removal in BACR were the Grau second-order kinetic model with an a value of 0.1382 and a b value of 1.0776, and the Stover-Kincannon kinetic model with an Rmax of 5.8 g COD/L.day and a KB of 6.24 g COD/L.day.